Environmental Literacy Shaping Educational Research: Trends, Knowledge Networks, and Future Pathways - Lintang Auliya Kurdiati (Journal of Environmental and Science Education, 2026)
This study aims to provide a comprehensive overview by tracing the development of environmental literacy research in education between 2015 and 2025. A bibliometric mapping and systematic literature network analysis was conducted using the Scopus database, applying PRISMA guidelines to refine an initial dataset of 6,355 records into 59 eligible publications. Analytical tools, including Biblioshiny, VOSviewer, and Microsoft Excel, were employed to generate descriptive statistics and science-mapping visualizations. The findings indicate a steady growth of publications, with Indonesia, China, and the United States emerging as leading contributors. The most cited works focus on large-scale surveys, eco-school programs, and problem-based pedagogies. Thematic mapping and co-occurrence analyses reveal dominant clusters around environmental education, curriculum innovation, sustainability, and teacher development, alongside emerging research fronts such as climate change and indigenous knowledge integration.